Rational Belief: A Critical Review of the Book Faith and Reason - Ghasem Pour Hasan (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Rationality theory is considered as one of the most important and fundamental approaches in the history of philosophy of religion. The conflict of reason and faith has a long history. Defending rationality against the domination of the faithism in Christianity should be regarded as an effective and important approach.Swin Burne with an important book titled “Faith and Reason” tried to restudy the importance of rational approach to religious beliefs and prepositions. In this book, he tried to provide a reinterpretation of the theory of rationality of belief. This work is the third collection of his writings in theism. He aimed to show the fundamental role of reason in epistemic justification of religious beliefs.His main question in this book: how to justify faith and religious beliefs with what kind of rational evidence, a belief can be justified? The present review aims to evaluate and criticize Swin Burne’s rational justification in his religious beliefs.